Directions of the research into a style in wooden architecture of Siberia - Gruzdeva, Evgeniya (project baikal, 2021)
Globalization and widespread active introduction of architectural forms, techniques, materials and building technologies pose a problem of finding regional identity, particularity and uniqueness of the style in architecture. Consideration of history and traditions of regional architecture is one of the ways to reveal this identity and uniqueness. Wooden architecture is traditional for Siberia. It has hardly evolved stylistically since the 1920s. Studying stylistic formation in wooden architecture of Siberia in the late 19th – early 20th centuries, including modern, will help to identify the peculiarities of the local style and culture. The style can be considered from the point of view of philosophy of architecture and art as a unique manifestation of regional culture, as one of the ways to create (recreate) cultural identity, particularity and uniqueness, and as a source of information on a variety of techniques and forms of wooden architecture in Siberia.
Keywords: Siberia; wooden architecture; modern; identity; regional architecture